Kandungan Mineral Beberapa Galur Harapan Padi Sawah - Gunarsih, Cucu; Mejaya, Made J.; Indrasari, Siti Dewi (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Rice as staple food is consumed as a source of energy and protein, but also contains minerals and vitamins. This study was aimed to obtain information on mineral contents of rice lines obtained from the bio-fortification program. The research was conducted at the Experiment Farm of the Rice Research Installation Sukamandi, during Wet Season of 2007/2008. A total of 26 rice varieties/lines with high yielding potential and high Fe and Zn contents in the grain were planted in 4 m x 5 m experimental plots with a spacing of 25 cm x 25 cm. The experiments were arranged in a randomized block design with three replications. Samples of grain harvested from each plot were milled using a Satake mini grinder that produces milled rice with an 80% milling degree. Analysis of the mineral content of rice from the varieties/lines was tested using an ICP (Inductivity Couple Plasma) at the Waite Analytical Service Laboratory, University of Adelaide, Australia. The results indicated a wide diversity in the mineral contents (Ca, P, Mg, Na, K, S, Fe, Zn, and Mn) of the milled rice of the tested rice varieties/lines. Six lines produced milled rice rich in macro minerals (Ca, P, and K) and have a potential to be released as varieties with high macro mineral contents. Seven other rice lines produced high levels of Fe and Zn and are recommended as candidate for high yielding rice varieties with high micro mineral contents.